2008
DOI: 10.29333/ejgm/82566
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Poisonings in the South Marmara Region of Turkey

Abstract: Aim:The aim of this study is to describe the characteristics of medico-legal autopsies of fatal poisonings in the south Marmara region, Turkey, in the period of 1996-2003, in order to provide further data for the characterisation of fatal poisonings, because there is a scarcity of such information from Turkey.Methods: Of the 4242 autopsied cases, 415 (9.8%) deaths due to poisonings were examined; 26.8% females and 73.2% males. The mean age was 40.1±19.2 years old (range 0-88).Results: The three most common typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
2
13
1
Order By: Relevance
“…This suggests that unintentional CO poisoning has a high prevalence in this region of the country. This is in part consistent with previous research conducted in Tehran (Sheikhazadi et al, 2010) and the northern part of the country (Ahmadi et al, 2010) as well as in Turkey (Fedakar and Tu¨rkmen, 2008;Tu¨fekc¸i, Ç urgunlu, & S¸irin, 2004), a neighbouring country with the same potential for CO poisoning (e.g. cold weather, especially during the winter months).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests that unintentional CO poisoning has a high prevalence in this region of the country. This is in part consistent with previous research conducted in Tehran (Sheikhazadi et al, 2010) and the northern part of the country (Ahmadi et al, 2010) as well as in Turkey (Fedakar and Tu¨rkmen, 2008;Tu¨fekc¸i, Ç urgunlu, & S¸irin, 2004), a neighbouring country with the same potential for CO poisoning (e.g. cold weather, especially during the winter months).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the results of this study indicated that domestic gas appliances were implicated in almost all of the incidents, which is also similar to observations by Sheikhazadi et al (2010) who found the conventional heating or cooking appliances were responsible for the largest numbers of unintentional CO deaths. However, this result is not in agreement with the findings from Tu¨fekc¸i et al (2004) and Fedakar and Tu¨rkmen (2008) who reported that dysfunctioning coal or wood stoves were responsible for most CO-related poisoning incidents in Turkey.…”
Section: Discussioncontrasting
confidence: 80%
“…Deaths from mushroom poisoning, due to the ingestion of mushrooms containing amatoxins, seem to be increasing both in Turkey and worldwide (1). The alpha-amanitin (α-AMA) found in Amanita phalloides (also called the death cap mushroom) is one of the most toxic agents, and it is responsible for more than 90% of the cases of deadly mushroom poisoning (2).…”
Section: Introductionmentioning
confidence: 99%
“…Durak (6) reported the rate of CO poisoning in autopsied deaths as 4.74% between years 1995 and 1998. Fedakar et al (9) was found this ratio as 4.2% in the south Marmara region between 1996 and 2003 years. The decrease in this ratio can be explained by consciousness of the society and sufficient precautions towards to CO poisoning.…”
Section: Discussionmentioning
confidence: 86%
“…CO poisoning is a common cause of toxicological morbidity and mortality in the United States (17). In our country, the most common cause of fatal poisoning was CO poisoning (9,12,(18)(19).…”
Section: Discussionmentioning
confidence: 88%